2005
DOI: 10.1002/jccs.200500145
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of 2-(Chromon-2/3-yl)-3-(5-thione-4-hydro-1,3,4-thiadiazol-2-yl)-4-oxo-thiazolidine

Abstract: 2-Formylchromones and 3-formylchromones as the first materials singly reacted with 2-amino-5-mercapto-1,3,4-thiadiazole to give the corresponding Schiff bases, which on cyclocondensation with mercaptoacetic acid in 1,4-dioxane yielded target compounds named 4-oxo-thiazolidines. The structures of all the synthetic compounds were confirmed by elemental analysis and IR, 1 H NMR, LC-MS (ESI) spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…6,7 Chromones not only have been extracted from natural products, but also synthesized by chemical methods. 8 In studies to improve the bioactivity of chromones, chemists have found that chromone-linked heterocyclic frameworks have a broad biological activity, especially at the C-3 position, with strong propensities to act as antitumor, antibacterial, antivirus, antimicrobial, and antiphlogistic agents. 9 Several flavonoid and chromone derivatives have also been found with inhibitory activity against the AR enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Chromones not only have been extracted from natural products, but also synthesized by chemical methods. 8 In studies to improve the bioactivity of chromones, chemists have found that chromone-linked heterocyclic frameworks have a broad biological activity, especially at the C-3 position, with strong propensities to act as antitumor, antibacterial, antivirus, antimicrobial, and antiphlogistic agents. 9 Several flavonoid and chromone derivatives have also been found with inhibitory activity against the AR enzyme.…”
Section: Introductionmentioning
confidence: 99%